Aplikasi Pemberian Ekstrak Bawang Merah (Allium Cepa L.) Terhadap Pertumbuhan Stek Batang Gaharu (Aquilaria malaccensis Lam.) - P Ponisri; Syaiful Maliki; Bernadus Aran (Fapetrik-UMPAR, 2022)
Aquilaria malaccensis Lam. is a gaharu-producing plant with excellent quality and high social, cultural, and economic values. Gaharu is one of the non-timber forest products with many uses, namely as a raw material for medicines, cosmetics, perfumes, incense, and preservative accessories. Gaharu is quite rare, although its cultivation can be done generatively or vegetatively. In connection with cultivation activities, quality agarwood seeds are needed. One way to do this is by giving Growth Regulatory Substances (ZPT). This study aims to determine the effect of different concentrations of shallot extract on the growth of gaharu (Aquilaria malaccensis Lam) stem cuttings. This study was arranged in a completely randomized design (CRD) consisting of 5 treatments and 3 replications, and each treatment used 5 stem cuttings. The treatment consisted of ZPT from shallots which consisted of 5 concentrations, namely: without ZPT, concentrations of 10%, 20%, 30%, and 40%. The data obtained were analyzed by analysis of variance (ANOVA), and a 5% BNT test was performed. The concentration of shallot extract significantly affected the growth of stem cuttings of Aquilaria malaccensis Lam, best at a concentration of 40%.